A Supermarket Anti-Theft Scanner : digiSCAN - Benjamin Kommey; Elvis Tamakloe; Eliel Keelson (Journal of Innovation Information Technology and Application (JINITA), 2022)
Supermarket shopping is an essential part of the livelihood of most people around the world. Consumers can acquire items essential for their daily activities. However, in an ever-evolving world with an increasing population and increasing crime rates, supermarket theft is becoming a prevalent problem with supermarket owners spending large sums of money on hiring security often with little effect. Organized Retail Crime (ORC) costs the retail industry approximately $30 billion each year, with 71.3% of retailers reporting an increase in ORC year-over-year. With the current global economic conditions, high labor costs are longer feasible. Consumers also face the issue of paying for items they did not select. Advanced camera systems, for some, may be an escape however, this approach is not feasible for all aspects of shopping and in underdeveloped countries that have technical constraints. The advent of digitization has helped improve the livelihood of consumers in Ghana. Currently, many large-scale retailers are oblivious to some of these advancements. The oblivion of the management of such retail services results in the loss of products, customer dissatisfaction, and the mismanagement of untracked products by employees. To reduce theft and the mismanagement of products by employees, a smart antitheft system should be deployed in supermarkets; at the till and before the exit of supermarkets to ensure all products leaving the store are paid for and accounted for. The system consists of a deactivation and theft detection system. The product is deactivated by the store attendant at the till when the customer pays for the product. However, if a customer crosses the initial warning zone without paying, a warning sound is triggered and after the customer crosses the final warning zone, the alarm is triggered indicating an attempted theft by the customer. A log of products is also kept ensuring employees are not stealing products. This paper presents a smart way of detecting theft during supermarket shopping using Radio Frequency Identification (RFID) readers and tags, a microcontroller-based control system, a database server, and an Integromat.